1997
DOI: 10.1103/physreve.56.7132
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of giant lipid bilayer vesicles in shear flow

Abstract: We describe experimental studies of the deformation of giant lipid bilayer vesicles in shear flow. The experiments are carried out with a counterrotating Couette apparatus. The deformation depends on the mechanical properties of the lipid bilayer, the vesicle radius, and the viscosity of the surrounding Newtonian liquid. We show that the relevant mechanical parameter is the bending rigidity. A simple model has been developed that describes the deformation of a vesicle. This model takes thermal undulations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(145 citation statements)
references
References 20 publications
6
132
3
Order By: Relevance
“…In contrast, the nonequilibrium dynamics of lipid bilayer membranes has been studied only to a limited extent. Experimental studies 7,8,9,10 of vesicle behavior in unbounded shear flow observe that in weak flows, and when the inner and outer fluids are the same, the vesicle deforms into a tanktreading stationary prolate ellipsoid with an inclination angle close to π/4 with respect to the flow direction; however, in striking contrast to drops, when the fluid inside is more viscous than outside the vesicle undergoes a tumbling motion. Numerical simulations 11,12,13 and analytical theories 14,15,16 of vesicle microhydrodynamics attempt to elucidate such experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the nonequilibrium dynamics of lipid bilayer membranes has been studied only to a limited extent. Experimental studies 7,8,9,10 of vesicle behavior in unbounded shear flow observe that in weak flows, and when the inner and outer fluids are the same, the vesicle deforms into a tanktreading stationary prolate ellipsoid with an inclination angle close to π/4 with respect to the flow direction; however, in striking contrast to drops, when the fluid inside is more viscous than outside the vesicle undergoes a tumbling motion. Numerical simulations 11,12,13 and analytical theories 14,15,16 of vesicle microhydrodynamics attempt to elucidate such experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…This non-equilibrium problem has revealed a variety of new physical effects and became a subject of intense experimental and theoretical studies. Laboratory experiments [1,2,3,4,5] have shown that the vesicles immersed in a shear flow exhibit at least two qualitatively different types of behavior, either tank-treading or tumbling motion. In the tank-treading regime a vesicle shape is stationary, it is ellipsoid oriented at an angle with respect to the shear flow.…”
mentioning
confidence: 99%
“…whereâ is some dimensionless operator, reflecting all viscous mechanisms, the Z-axis of our reference frame is chosen to be directed opposite to the angular velocity ω, and F (3) is an expansion up to third order in u of the free energy (1). Note that the elongation and the rotation parts of the external flow are separated in Eq.…”
mentioning
confidence: 99%
“…However, it was demonstrated that lipid vesicles without an attached polymer network may serve as a simple model which already captures the basic physics of the fluid-structure interaction problem. We note that the dynamics of RBC and vesicles in fluid flow has been studied both experimentally (see [1,2,19,20,26,37]) and theoretically (cf. [6,7,21,22,32,34]).…”
Section: % Iterationmentioning
confidence: 99%
“…at each time step the BE/BE FE-IB then amounts to the computation of z (k+1) , 0 ≤ k ≤ M − 1, as the solution of the nonlinear system 19) where the nonlinear mapping G(·; t k+1 ) :…”
Section: Fully Implicit Fe-ibmentioning
confidence: 99%